2021
DOI: 10.1111/pedi.13255
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mood, diabetes‐specific and COVID ‐19‐specific experiences among parents of early school‐age children with type 1 diabetes during initial months of the COVID ‐19 pandemic

Abstract: Objective The current study explored pre‐pandemic sociodemographics, medical characteristics, social/family support, and mood symptoms, and current COVID‐19 experiences as predictors of mood, positive/negative diabetes‐specific experiences, and COVID‐19‐specific distress among parents of children with type 1 diabetes during the COVID‐19 pandemic. We hypothesized that parents from marginalized backgrounds, youth with higher pre‐pandemic A1c and no CGM use, parents with lower pre‐pandemic social/family support a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Items include questions about changes in diabetes management, mood, living situations during the pandemic, and the extent to which people in and around the family have come into contact with the COVID-19 virus. A team of pediatric psychologists developed the COVID-19 survey for use in ongoing studies, 6,15 and sample questions include “In what ways has COVID-19 impacted your T1DM management?” and “Overall, how worried or anxious has YOUR CHILD been about the COVID-19 pandemic?” In the current analyses, the Impact on Diabetes Management (parent/teen report) subscale and Impact on Mood (parent/teen report) subscale were used. Questions on the diabetes management and mood subscales are scaled on a 5-point Likert scale and summed, with higher scores indicating a greater impact of COVID-19 on diabetes management and teen mood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Items include questions about changes in diabetes management, mood, living situations during the pandemic, and the extent to which people in and around the family have come into contact with the COVID-19 virus. A team of pediatric psychologists developed the COVID-19 survey for use in ongoing studies, 6,15 and sample questions include “In what ways has COVID-19 impacted your T1DM management?” and “Overall, how worried or anxious has YOUR CHILD been about the COVID-19 pandemic?” In the current analyses, the Impact on Diabetes Management (parent/teen report) subscale and Impact on Mood (parent/teen report) subscale were used. Questions on the diabetes management and mood subscales are scaled on a 5-point Likert scale and summed, with higher scores indicating a greater impact of COVID-19 on diabetes management and teen mood.…”
Section: Methodsmentioning
confidence: 99%
“…Items include questions about changes in diabetes management, mood, living situations during the pandemic, and the extent to which people in and around the family have come into contact with the COVID-19 virus. A team of pediatric psychologists developed the COVID-19 survey for use in ongoing studies, 6,15 and sample questions include "In what ways has COVID-19 impacted your T1DM management?" and "Overall, how worried or anxious has YOUR CHILD been about the COVID-19 pandemic?"…”
Section: Methodsmentioning
confidence: 99%
“…Noticeably, the odds ratio for the severity of Type-1 diabetic patients were much higher than Type-2 diabetic patients [25]. Another RCT with children with Type-1 diabetes in the US suggested that preintervention and social support improved the children to manage COVID-19 pandemic-related stress and depressive symptoms for the children and their parents [26].…”
Section: What Is the Clinical Evidence On The Relationships Between C...mentioning
confidence: 99%
“…Recently, studies have described the experience of managing diabetes in children during the COVID-19 pandemic [ 78 80 ]. Our team followed a cohort of parents of children ( n = 100) who were diagnosed with T1D at a young age (1–6 years, pre-pandemic) who had completed a behavioral trial more than 6 months prior (enrolled between 2015–2019), and obtained data for 2 additional follow-up times points during the pandemic (Summer 2020, Winter 2021 [ 81 ]). During Summer, 2020, parents of children with T1D (M age = 6.74 years) who reported experiencing more pandemic-related life disruptions during the initial months of the pandemic also reported more negative diabetes-specific experiences as well as COVID-19-specific distress.…”
Section: Current Issuesmentioning
confidence: 99%
“…During Summer, 2020, parents of children with T1D (M age = 6.74 years) who reported experiencing more pandemic-related life disruptions during the initial months of the pandemic also reported more negative diabetes-specific experiences as well as COVID-19-specific distress. Further, parents of young children with T1D who had higher social support pre-pandemic reported fewer depressive symptoms during Summer, 2020 [ 81 ].…”
Section: Current Issuesmentioning
confidence: 99%